A History of the FTAA - Nelson, Marcel. author. aut Link
XIV, 273 p.
Keywords: Providing a critical account of the collapse of the FTAA negotiations and alterations to power relations in the Americas, this book argues that the collapse was rooted in a "crisis of authority" prompted by growing opposition in the Americas to US leadership and the neo-liberal reforms that had been promoted by Washington since the 1980s.